Oral health profile of postbariatric surgery individuals: A case series - Negin Taghat; Karin Mossberg; Peter Lingström; Sofia Björkman; Anna Lehrkinder; Malin Werling; Anna‐Lena Östberg (Wiley, 2021)
Abstract Objectives To describe the oral health profile of individuals who had undergone gastric bypass surgery (GBP) or sleeve gastrectomy (SG) to generate hypotheses for further studies. Material and Methods Fourteen individuals treated with GBP or SG surgery ≥ 2 years ago and with observed and/or perceived oral problems were recruited to a case series. The documentation included clinical and radiographic examinations, biomedical sampling, and self‐reported diet and questionnaires. The results are presented descriptively. Results: The age range was 31 to 66 years and all had a BMI > 25 (range 25.4-44.7). Only four participants were fully dentate. Eleven out of 14 individuals exhibited severe decay. A majority had poor oral hygiene and high bacterial counts. The flow rates of unstimulated saliva were extremely low and hyposalivation was present in ten of the fourteen cases. Most perceived several oral health problems, such as chewing difficulty and tooth hypersensitivity. Conclusions Individuals who had undergone GBP or SG surgery had poor clinically diagnosed oral health and perceived oral health problems. Longitudinal studies are needed to monitor the patients' oral health, from before bariatric surgery to long‐term postoperatively.